The methodology and its impact on reading and writing - Raguá Rueda, Gloria Elena; Delgado Cabeza, Ruby Alejandra; Monsalve Maldonado, Nohora Rocio (Rastros Rostros, 2023)
The fundamental purpose of education is to form integral human beings, capable of creating, producing and facing the challenges that life offers; for this, it is necessary to educate in and for reading and writing, establishing a direct relationship between the enjoyment and ability to read and write all types of texts, turning these processes into playful and gratifying activities, thus achieving a quality educational system.